Presence system using RFID and ESP32 CAM based on Internet of Things - Kelvin; Eliza, Fivia; Elvanny Myori, Dwiprima; Faradina, Nevi (Department of Electrical Engineering Universitas Negeri Padang, 2024)
RFID enables fast and accurate user identification via radio waves, while ESP32-CAM, an ESP32 microcontroller-based camera module, adds a layer of security through visual verification. Optimizing the attendance process by reducing the time required for attendance recording, thereby reducing disruption to daily activities. The RFID and ESP32Cam Attendance System Based on the Internet off things